PENGARUH KOMITMEN ORGANISASIONAL DAN PENGEMBANGAN KARIR SERTA SELF EFFICACY TERHADAP KINERJA KARYAWAN PADA PT. BANK BUKOPIN SYARIAH CABANG SAMARINDA - Ade Wulan Islamiati; Sukisno Selamet Riadi; Siti Mari (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
Ade Wulan Islamiati, 2019. the Effect of Organizational Commitment and Career Development, with Self-Efficacy toward Performance Employee of PT. Bank Bukopin Syariah Cabang Samarinda, under the guidance of Prof. Dr. Sukisno S. Riadi, SE., MM. and Dr. Siti Maria, SE., Msi.The purpose of the reaserch to examine whether the organizational commitment, career development, and self-efficacy towards performance employee of PT. Bank Bukopin Syariah Cabang Samarinda. The independent variable of this research as organizational commitment, career development, and self-efficacy. While dependent variable is performance employee. This research was conducted on of PT. Bank Bukopin Syariah Cabang Samarinda which consist 60 respondents.The research is quantitative research. The data collection use questionnaire by examining organizational commitment, career development, and self-efficacy. The data analysis use multiple linear regression. These result indicate the variable organizational commitment, career development, and self- efficacy has significant effect on performance employee.